Extensively drug-resistant Mycobacterium tuberculosis from aspirates, Rural South Africa. - Heysell, Scott K; Moll, Anthony P; Gandhi, Neel R; Eksteen, Francois J; Babaria, Palav; Coovadia, Yacoob; Roux, Lynn; Lalloo, Umesh; Friedland, Gerald; Shah, N Sarita (Emerging infectious diseases, 2010)
The yield from aspirating lymph nodes and pleural fluid for diagnosing extensively drug-resistant (XDR) tuberculosis is unknown. Mycobacterium tuberculosis was cultured from lymph node or pleural fluid aspirates of 21 patients; 7 (33%) cultures grew XDR M. tuberculosis. Additive diagnostic yield for XDR M. tuberculosis was found in parallel culture of sputum and fluid aspirate.
Keywords: Adult; AIDS-Related Opportunistic Infections; Antitubercular Agents; Biopsy, Fine-Needle; Culture Media; Drug Resistance, Multiple, Bacterial; Extensively Drug-Resistant Tuberculosis; Female; HIV Infections; Humans; Lymph Nodes; Male; Microbial Sensitivity Tests; Mycobacterium tuberculosis; Pleural Effusion; Rural Population; South Africa